Perancangan Sistem Informasi Dengan PHP Dan MYSQL Untuk Pendaftaran Sekolah Di Masa Pandemi - Mugi Raharjo; Musriatun Napiah; Rian Septian Anwar (Computer Science (CO-SCIENCE), 2022)
During the current Covid-19 pandemic, a platform such as a website is needed to facilitate the process and activities of new student admissions in the field of education, the activity in question is holding a selection of new student admissions in schools. In the process of admitting new students, there are still a lot of schools that still use the system manually or face to face in the admissions process, so that the level of efficiency and security in order to maintain health protocols can be met. In this design, the author conducted a case study in one of the kindergartens in Jakarta which still applies a manual system so that in this pandemic era it is very effective. Students don't need to be bothered to come to school during this pandemic. In terms of education on the website, we provide guidance to parents on how to use the website via whatsapp video call or Zoom Meeting to make it easier. For that we tried to make the website, which is an information system that is used for new student admissions based on the website to make it easier for parents to register for school for their children. And the selection of the website platform was chosen to make it easier for parents to open this service without having to install applications that would normally take up memory on smartphone devices, we created this website with Php and My Sql. The results of this study indicate that this system is able to manage the process of accepting new students for this school.